Recent advances in natural polysaccharides for type 2 diabetes management: sources, structural characteristics, and mechanistic insights - Liu, Zexiang; Wang, Hanlong; Gong, Xiujuan; Jiang, Xiao; Yang, Kangyi; Jiang, Linfang; Wang, Zhihui; Tong, Qiaozhen (Frontiers in Pharmacology, 2025)
The global prevalence of type 2 diabetes mellitus (T2DM) continues to rise, posing significant challenges for existing therapeutic strategies, which are often limited by poor bioavailability, high cost, and adverse effects. Natural polysaccharides have emerged as promising metabolites due to their broad sources, favorable safety profiles, and stable efficacy. This review systematically summarizes the sources, structural characteristics, and mechanisms of action of natural polysaccharides with anti-T2DM activity, with a particular focus on their multi-target regulatory effects in mitigating T2DM and its complications. By integrating structural diversity—such as molecular weight, glycosidic linkage patterns, and branching architecture—with functional outcomes across key pathogenic pathways including insulin resistance, inflammation, oxidative stress, gut microbiota dysbiosis, and mitochondrial dysfunction, this work elucidates fundamental structure-activity relationships. The review not only bridges existing knowledge gaps in multi-mechanistic integration but also provides a conceptual framework for the structure-based development of polysaccharide-based therapeutics against T2DM, highlighting future research directions.